간동맥색전술로 치료한 고칼슘혈증을 동반한 경화성 간세포암 1예 - 이돈; Don Lee; 김인한; In Han Kim; 김선후; Seon Hu Kim; 이진우; Jin Woo Lee; 최원; Won Choi; 이돈행; Don Haeng Lee; et al. (The Korean journal of medicine, 2000)
The sclerosing hepatocellular carcinoma is a histopathologically unusual subtype of primary hepatocellular carcinoma characterized by intense fibrous stroma in which the tubular neoplastic structures are embedded. It has been reported that hypercalcemia is much more frequently associated up to 69% in this subtype than in other subtypes of primary hepatocellular carcinoma. As we know, uncontrolled hypercalcemia may result in fatal outcome, and it was reported that hypercalcemia associated with hepatocellular carcinoma could be controlled with the resection of the tumor when it was possible. We report a case of sclerosing hepatocellular carcinoma with hypercalcemia in which the hypercalcemia was controlled with transcatheter arterial chemoembolization (TACE).(Korean J Med 59:104-108, 2000)